Serological biomarkers for acute mesenteric ischemia - Obulkasim Memet; Lin Zhang; Jie Shen (2019)
Acute mesenteric ischemia (AMI) defines a complex of conditions characterized by an interruption of the splanchnic circulation, leading to insufficient oxygen delivery or utilization to fill the metabolic needs of the visceral organs. Early diagnosis and immediate therapy are the cornerstones of early ischemia to reach a successful outcome and are necessary to reduce the high mortality. Although there is still lack of specific biomarkers to assist the diagnosis of AMI in clinical practice, there are several biomarkers with high specificity, may become a potential tools in early diagnosis of AMI, including intestinal fatty acid binding protein (I-FABP), a-glutathione S-transferase (a-GST), D-dimer, L- and D-lactate, citrulline, ischemia modified albumin, procalcitonin (PCT). However, they use in clinical limited duo to the many studies about these makers finished with small patient populations, and heterogeneous among these populations. This review describes the etiology of AMI, the current most studied promising biomarkers, the current research situation and future of biomarker research.